SETTLEMENT OF DEFECTS IN MURABAHAH FINANCING AT BANK ACEH SYARIAH REGIONAL BIREUEN, INDONESIA - Afra, Cut; Eriyanti, Nahara; Mohamed Arif, Nasr (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2023)
This research aims to investigate the procedure for addressing problems in murabahah finance resulting from debtor default. This study uses empirical juridical research methodology, which involves gathering data through interviews, document and report analysis, and other secondary sources. The research findings indicate that default is primarily caused by external factors, including the deteriorating business condition or failure of the customer's business, the customer's unfavourable character, and issues in the installment payment process such as delayed debt payments. The second cause pertains to an internal issue when the debtor fails to fulfil the promised payment within the agreed timeframe. In order to address this default, Bank Aceh Bireuen Branch conducted deliberations guided by the principle of justice (al-ilah) between the bank and the member responsible for the default, in accordance with the muamalah concept and relevant rules.